2023
DOI: 10.29020/nybg.ejpam.v16i1.4656
|View full text |Cite
|
Sign up to set email alerts
|

Convex Hop Domination in Graphs

Abstract: Let G be an undirected connected graph with vertex and edge sets V (G) and E(G), respectively. A set C ⊆ V (G) is called convex hop dominating if for every two vertices x, y ∈ C, the vertex set of every x-y geodesic is contained in C and for every v ∈ V (G) \ C, there exists w ∈ C such that dG(v, w) = 2. The minimum cardinality of convex hop dominating set of G, denoted by γconh(G), is called the convex hop domination number of G. In this paper, we show that every two positive integers a and b, where 2 ≤ a ≤ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Moreover, they have obtained some exact values or bounds of the parameter on the generalized graph, some families of graphs, and graphs under some operations via characterizations. Some interesting studies related to zero forcing hop domination can be found in [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have obtained some exact values or bounds of the parameter on the generalized graph, some families of graphs, and graphs under some operations via characterizations. Some interesting studies related to zero forcing hop domination can be found in [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they derived some bounds and formulas for some special graphs and graphs under some binary operations. Some studies related to hop independent sets, its variations, and other hop-related concepts can be found in [3,9,10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have characterized the vertex cover hop dominating sets in some special graphs, join, and corona of two graphs, and obtained the exact values or bounds of the parameter of these graphs. Some studies related to vertex cover hop domination can be found in [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%